2017
DOI: 10.5713/ajas.17.0063
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Bacillus subtilis against Salmonella infection in the microbiome of Hy-Line Brown layers

Abstract: ObjectiveThis study investigated the effects of Bacillus subtilis CSL2 (B. subtilis CSL2) administration before Salmonella challenge on the fecal microbiota and microbial functionality of Hy-line Brown (HLB) laying hens.MethodsFecal samples were collected from control (CON), Salmonella-infected (SAL) and Salmonella-infected, probiotic-treated (PRO) groups before and after Salmonella challenge for microbiome analysis using 16S rRNA gene pyrosequencing.ResultsInfection with Salmonella led to decreased microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
(54 reference statements)
3
17
0
Order By: Relevance
“…Probiotic‐treated Salmonella ‐challenged chickens exhibited a reduction in Proteobacteria compared with those just Salmonella challenged. The shift in bacterial microbiota demonstrated a similar trend as that reported for S. Gallinarum in other research (Oh, Pajarillo, Chae, Kim, & Kang, ; Oh, Pajarillo, Chae, Kim, Yang, & Kang, ). In our study, we determined that the number of Lactobacillus and Oscillospira in the ProSal group was higher than in the Cont and Sal groups.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Probiotic‐treated Salmonella ‐challenged chickens exhibited a reduction in Proteobacteria compared with those just Salmonella challenged. The shift in bacterial microbiota demonstrated a similar trend as that reported for S. Gallinarum in other research (Oh, Pajarillo, Chae, Kim, & Kang, ; Oh, Pajarillo, Chae, Kim, Yang, & Kang, ). In our study, we determined that the number of Lactobacillus and Oscillospira in the ProSal group was higher than in the Cont and Sal groups.…”
Section: Discussionsupporting
confidence: 88%
“…The results of apparent clustering by group suggested that chicken developed distinct microbial signatures attributable to probiotic administration and Salmonella infection. Similar results were observed in the intestinal population of poultry fed with Bacillus strains as probiotics or infected with Salmonella (Oh, Pajarillo, Chae, Kim, & Kang, ; Oh, Pajarillo, Chae, Kim, Yang, & Kang, ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Animals infected with strains of Salmonella exhibited a significant increase in Proteobacteria (Videnska et al ). Probiotic administration in pigs and broilers was correlated with increased abundance of Firmicutes and decreased abundance of Proteobacteria (Oh et al ; Oh et al ). Members of the Helicobacteraceae family, particularly Helicobacter , are associated with gastrointestinal diseases in many animals (Fox and Lee ; Solnick and Schauer ).…”
Section: Discussionmentioning
confidence: 99%